2012
DOI: 10.1051/0004-6361/201219792
|View full text |Cite
|
Sign up to set email alerts
|

The enigmatic nature of the circumstellar envelope and bow shock surrounding Betelgeuse as revealed byHerschel

Abstract: Context. The interaction between stellar winds and the interstellar medium (ISM) can create complex bow shocks. The photometers on board the Herschel Space Observatory are ideally suited to studying the morphologies of these bow shocks. Aims. We aim to study the circumstellar environment and wind-ISM interaction of the nearest red supergiant, Betelgeuse. Methods. Herschel PACS images at 70, 100, and 160 μm and SPIRE images at 250, 350, and 500 μm were obtained by scanning the region around Betelgeuse. These da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
92
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 90 publications
(153 reference statements)
10
92
0
Order By: Relevance
“…A few of them are identified as evolved massive stars and three of them are red supergiants with detected bow shocks, i.e. Betelgeuse (Noriega-Crespo et al 1997;Decin et al 2012), µ Cep (Cox et al 2012) and IRC−10414 . Consequently, and because these stars will explode as core-collapse supernova, their circumstellar medium is of prime interest in the study of aspherical supernova remnants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few of them are identified as evolved massive stars and three of them are red supergiants with detected bow shocks, i.e. Betelgeuse (Noriega-Crespo et al 1997;Decin et al 2012), µ Cep (Cox et al 2012) and IRC−10414 . Consequently, and because these stars will explode as core-collapse supernova, their circumstellar medium is of prime interest in the study of aspherical supernova remnants.…”
Section: Introductionmentioning
confidence: 99%
“…The works by van Marle et al (2011) and Decin et al (2012) tailor models to Betelgeuse's bow shock and estimate in the context of recent observations (Cox et al 2012) how the drag force on dust grains modifies the evolution of its contact discontinuity. The effects of the mass loss and space velocity on the shape and luminosity of bow shocks around red supergiant stars is investigated in Meyer et al (2014, hereafter Paper I).…”
Section: Introductionmentioning
confidence: 99%
“…Ueta 2006), systemic motion relative to the local interstellar medium (e.g. Decin et al 2012), magnetic fields (e.g. Pérez-Sánchez et al 2013;van Marle et al 2014), or binarity (Soker 1997;Huggins 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Numerical models by Brighenti & D'Ercole (1995) showed both Rayleigh-Taylor (RT) and KelvinHelmholtz (KH) instabilities for the general case. Subsequent attempts by van Marle et al (2011) and Decin et al (2012) to model the bow shock of α-Orionis showed large instabilities that would be observable with Herschel, if they exist. The absence of instabilities has been explained by Mohamed et al (2012) and Appendix A and associated movies are available in electronic form at http://www.aanda.org Mackey et al (2012) as evidence that the bow shock is still in an early stage of formation and that the instabilities have not yet had time to develop.…”
Section: Introductionmentioning
confidence: 99%